Intermediate expression of CCRL1 reveals novel subpopulations of medullary thymic epithelial cells that emerge in the postnatal thymus. - Ribeiro, AR (2014)
Cortical and medullary thymic epithelial cells (cTECs and mTECs, respectively) provide inductive microenvironments for T-cell development and selection. The differentiation pathway of cTEC/mTEC lineages downstream of common bipotent progenitors at discrete stages of development remains unresolved. Using IL-7/CCRL1 dual reporter mice that identify specialized TEC subsets, we show that the stepwise acquisition of chemokine (C-C motif) receptor-like 1 (CCRL1) is a late determinant of cTEC differentiation. Although cTECs expressing high CCRL1 levels (CCRL1(hi) ) develop normally in immunocompetent and Rag2(-/-) thymi, their differentiation is partially blocked in Rag2(-/-) Il2rg(-/-) counterparts. These results unravel a novel checkpoint in cTEC maturation that is regulated by the cross-talk between TECs and immature thymocytes. Additionally, we identify new Ulex europaeus agglutinin 1 (UEA)(+) mTEC subtypes expressing intermediate CCRL1 levels (CCRL1(int) ) that conspicuously emerge in the postnatal thymus and differentially express Tnfrsf11a, Ccl21, and Aire. While rare in fetal and in Rag2(-/-) thymi, CCRL1(int) mTECs are restored in Rag2(-/-) Marilyn TCR-Tg mice, indicating that the appearance of postnatal-restricted mTECs is closely linked with T-cell selection. Our findings suggest that alternative temporally restricted routes of new mTEC differentiation contribute to the establishment of the medullary niche in the postnatal thymus.